How does financial literacy affect investment decisions and customer profitability? The case of ActivoBank’s clients - Guerra, Sofia Maria de Alcântara Sá (2022)
In a time of economic uncertainty, financial literacy appears as an essential tool for an individual’s financial well-being, namely through effective investment decisions. These financial decisions also affect the demand for financial products offered by financial intermediaries, such as ActivoBank. In this research paper, we address the level of financial literacy of ActivoBank’s clients and we try to understand what sociodemographic factors influence it. Moreover, we examine how financial literacy affects clients’ investment decisions. Accordingly, we analyse if financial literacy is related to the returns each client generates to the bank, with the rationale that people who invest the most tend to generate higher profits, through the payment of fees. The main findings show that ActivoBank’s clients seem to have an overall level of financial literacy better than the Portuguese average. Moreover, gender and education are found to have a positive impact on financial literacy and marital status a negative one. Further, financial literacy is shown to positively impact saving, planning for retirement, and investing in riskier assets. Finally, results show that financial literacy doesn’t have a significant relationship with customer profitability.